Effects of Pear Juice on Weight Loss in Obese Adolescents - Purnamasari, Yulia; Hikmawati, Isna; Amelia, Vivi Leona; Linggardini, Kris (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Adolescents are highly vulnerable to nutritional problems, with obesity recognized as a global epidemic by the World Health Organization (WHO). In Indonesia, around 13.5% of individuals over 18 are overweight, and 28.7% are obese. Objective: This study aimed to examine the effect of pear juice consumption on weight loss among obese adolescents. Methods: A quasi-experimental study with a pre-test and post-test control group design was conducted. Participants were divided into intervention and control groups, each with 34 obese adolescents selected through purposive sampling. Data were analyzed using Paired t-Test and Independent t-Test at a significance level of </ 0.05. Results: Most respondents were male (55.9%), 75.0% were classified as obese based on BMI, and 60.3% had a genetic predisposition to obesity. The intervention group showed an average weight loss of 1.91 +/ 0.332 kg, while the control group had an average weight gain of 1.79 +/ 0.155 kg. Although weight loss in the intervention group was significant, the difference between groups was not statistically significant. Conclusion: Pear juice may help reduce weight in obese adolescents, possibly due to its fiber content that supports calorie regulation. Further studies with larger samples are recommended.